Assessing neighbourhood destination access for children: development of the NDAI-C audit tool. (November 2015) - Badland, Hannah; Donovan, Phil; Mavoa, Suzanne; Oliver, Melody; Chaudhury, Moushumi; Witten, Karen
Considerable societal changes across many countries have altered how children interact with their local environment, yet child-specific destination data have not been translated into a child-related destination accessibility index to further understand how neighbourhood locations support or hinder child mobility. Using data sourced from 238 9–11 year-old children living in Auckland, New Zealand, we aimed to: identify common destinations children travelled to; and develop a spatially derived objective index to quantify access to destinations that may support child mobility in the neighbourhood. Our findings show that children accessed a wide range of destinations during their daily activities, and the neighbourhoods that supported children's mobility tended to be located in more established areas, rather than newer greenfield developments.